Cross‐guide Moreno directional coupler in empty substrate integrated waveguide. Issue 5 (3rd May 2017) - Miralles, E.; Belenguer, A.; Esteban, H.; Boria, V.
Abstract: Substrate integrated waveguides (SIWs) combine the advantages of rectangular waveguides (low losses) and planar circuits (low cost and low profile). Empty substrate integrated waveguide (ESIW) has been proposed as a novel configuration in SIWs recently. This technology significantly reduces the losses of conventional SIW by removing its inner dielectric. The cross‐guide directional coupler is a well‐known low‐profile design for having a broadband waveguide coupler. In this paper a cross‐guide coupler with ESIW technique is proposed. In such a manner, the device can be integrated with microwave circuits and other printed circuit board components. It is the first time that a cross‐guide coupler is implemented in ESIW technology. The designed, fabricated, and measured device presents good results as a matter of insertion loss of 1 dB (including transitions), reflection under 20 dB, coupling between 19.5 and 21.5 dB, and directivity higher than 15 dB over targeted frequency range from 12.4 GHz to 18 GHz. The coupler implemented in ESIW improves the directivity when compared to similar solutions in other empty substrate integrated waveguide solutions. Key Points: First time that a cross‐guide Moreno coupler is implemented in empty substrate integrated waveguide The coupler has been manufactured; the prototype has excellent performance, with isolation above 15 dB in the whole band of the ESIW Prototype is integrated in a printed circuit